The Role of Brand Credibility and Consumer Engagement in Brand Expansion at PT Mayora - Noviana, Noviana (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This study investigates the effectiveness of brand credibility and consumer involvement in brand extension strategies at PT Mayora. Conducted through qualitative methods involving direct observation and interviews with PT Mayora consumers in Surabaya, the research reveals that the company has successfully implemented these strategies. The credibility of the brand significantly boosts consumer confidence in new product launches, fostering greater interest and involvement among consumers. These findings suggest that PT Mayora's approach contributes to increased sales and successful promotion of new products derived from brand extensions. The study emphasizes the importance of maintaining these successful strategies and encourages PT Mayora to continue building on its achievements. By consistently implementing effective brand extension strategies, PT Mayora can sustain its success, secure consumer trust, and remain competitive in the market. The research concludes that a combination of brand credibility and consumer involvement is a potent strategy for PT Mayora in navigating the market landscape, ensuring the company's continued growth and success in brand expansion.